PENGARUH KEWAJIBAN MODAL MINIMUM, FINANCING TO DEPOSIT RATIO, CASH RATIO, TERHADAP PROFITABILITAS DENGAN NON PERFORMING LOAN SEBAGAI VARIABEL INTERVENING PADA BANK UMUM 2020-2023 - Febri Ariyantiningsih; Randika Fandiyanto; Minullah Minullah (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), and Cash Ratio on Profitability with Non-Performing Loan (NPL) as an intervening variable in commercial banks listed on the Indonesia Stock Exchange (IDX) for the period 2020–2023. The study uses a quantitative approach with secondary data from the annual financial reports of 12 sample banks selected using purposive sampling techniques. The data were analyzed using Partial Least Square (PLS) with the help of SmartPLS 3.0 software. The results of the study indicate that: (1) CAR does not have a significant effect on NPL; (2) FDR does not have a significant effect on NPL; (3) Cash Ratio has a positive and significant effect on NPL; (4) CAR does not have a significant effect on Profitability; (5) FDR does not significantly affect Profitability; (6) Cash Ratio does not significantly affect Profitability; (7) NPL does not significantly affect Profitability; and (8), (9), and (10) NPL is not proven to mediate the relationship between CAR, FDR, and Cash Ratio on Profitability. Based on these findings, it can be concluded that of the three independent variables, only the Cash Ratio significantly affects NPL, but none of the variables have a significant effect on Profitability, either directly or indirectly through NPL mediation. The implications of this study emphasize the importance of prudent liquidity management and operational efficiency for banks, as well as the need for further research by adding other variables and expanding the scope of the study period..